2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32073
|View full text |Cite
|
Sign up to set email alerts
|

An Interdisciplinary Research Group’s Collaboration to Understand First-Year Engineering Retention

Abstract: is a Curriculum and Instruction PhD student and Graduate Research Assistant at the University of Louisville. Her research interests include interdisciplinary faculty development, STEM identity, retention of engineering students, the use of makerspaces in engineering education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…There are numerous reasons why the authors have identified interest as potentially one of the most influential of expectancy-value constructs. A recent study at our institution identified interest as the primary barrier for students [15]. In that study, the magnitude of interest was found to be a critical predictor for first-year retention.…”
Section: Influence Of Interest On Retention At Our Universitymentioning
confidence: 80%
“…There are numerous reasons why the authors have identified interest as potentially one of the most influential of expectancy-value constructs. A recent study at our institution identified interest as the primary barrier for students [15]. In that study, the magnitude of interest was found to be a critical predictor for first-year retention.…”
Section: Influence Of Interest On Retention At Our Universitymentioning
confidence: 80%
“…B. Speed School of Engineering students [16]. In that study, it was found that magnitude of interest is a critical predictor for J.…”
Section: Interest In Engineering and Potential Significance In Studen...mentioning
confidence: 91%